Light physical activity is positively associated with cognitive performance in older community dwelling adults. Issue 11 (November 2016) - Johnson, Liam G.; Butson, Michael L.; Polman, Remco C.; Raj, Isaac S.; Borkoles, Erika; Scott, David; Aitken, Dawn; Jones, Graeme
Abstract: Objectives: To evaluate the associations between an objective measure of different intensities of physical activity, upper- and lower-limb muscle strength and psychomotor performance and set-shifting domains of cognitive executive function in older adults. Design: A cross-sectional study. Methods: From the Tasmanian Older Adult Cohort Study, 188 community-dwelling older adults (53.7% female; mean age ± SD 63.98 ± 7.3 years) undertook 7-day physical activity behaviour monitoring using an accelerometer. Dynamometers were used to assess leg extension strength. The Trail Maker Tests were used to measure psychomotor processing speed and set-shifting performance. Results: When controlling for age, smoking history, alcohol intake, educational achievement and neuropsychological functioning, higher levels of light physical activity, but not sedentary behaviour or moderate or vigorous physical activity, was found to be associated with better set-shifting performance. Neither physical activity behaviour or muscle strength were found to be associated with psychomotor performance. In addition, older age, greater alcohol intake, and lower levels of educational attainment, verbal learning and memory performance were significantly associated with lower scores on the set-shifting task; whereas older age and reduced neuropsychological functioning were associated with lower psychomotor processing speed scores. Conclusions: Light physical activity is associated with higher executive functioning in community-dwelling older adults and this strengthens the evidence supporting exercise as a neuroprotective agent. Further studies are needed to understand why light physical activity behaviour positively influences executive functioning, and how such physical activity can be implemented into the daily routine of older adults.